Psychosocial Rehabilitation Programs from Emirati Culture perspective at Erada Center - A. Aljasmi (Emerging Trends in Drugs, Addictions, and Health)
All substance use patients on addiction treatment centers deserve to be treated to the highest professional and ethical standards by appropriately qualified, experienced healthcare professionals. Indeed, both the patients’ micro and macro systems involve stakeholders’ influences to informally or explicitly on their treatment. In addition, the UAE Federal Law No.8 of 2016 has a dramatic shift towards treatment where offenders will no longer have a court case if they voluntarily present themselves to the Addiction Treatment Unit seeking treatment. In addition to the Law No. 5 of 2015 of establishment of Erada Center in Dubai aims to treat the disease of substance use disorders and alcohol addiction, which result in negative psychological, economic, social and physical impacts. This presentation will give an overview about Erada Center Treatment Programs and how the cultural aspects was taken into consideration during the implementation process. The treatment programs are driven from trained clinicians through individual and group counselling include a variety of treatments used to treat behavioural health problems such as Matrix Model, 12 steps, CBT module, family intervention and spiritual programs. These programs were translated to Arabic language with review to take the cultural values of the patients into consideration. This presentation also will show the effectiveness of these programs from patient's recovery and relapse rates, and patient quality of life improvements. It will give an overview about psychosocial treatment standards that has been followed at Erada Centre. The Method of the research will be using internal and external secondary data; such as statistics, recovery and relapse rate, patients progress reports, and other national reports about substance abuse figures.